A cluster of Psittacosis cases in Lishui, Zhejiang Province, China, in 2021 - Yao, Wenwu; Chen, Xiuying; Wu, Zhuoying; Wang, Lingbo; Shi, Guoxiang; Yang, Zhangnv; Zhang, Yanjun; Wu, Beibei (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Psittacosis, caused by Chlamydia psittaci, is widespread throughout the world. In humans, C. psittaci infection may lead to severe conditions and complications, including sepsis and multiple organ failure. We report a cluster of cases caused by C. psittaci in Zhejiang Province, 2021, which led to one death and three cases of hospitalization. Methods The cases were confirmed by nest-PCR, RT-PCR, and mNGS. Results The four cases were related and the sequences obtained from the samples were closely correlated with those from Taiwan. Discussion This study is the first to report on the case of death from psittacosis in Zhejiang Province, and our results help to assess the disease and recommend effective measures to prevent further spread of C. psittaci.